Prevalence of visual impairment and associated vision related quality of life among older adults in an urbanized village in Delhi - ., Praveena; Kumar, Ashok; Barik, Rashmi Ranjan; Tiwari, Pradeep Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Vision impairment (VI) is a public health problem, of which the greatest burden is shared by older adults. This study was done to find out the prevalence of VI among older adults and its association with sociodemographic variables and vision related quality of life. Methods: This cross-sectional study was done in an urbanized village in east Delhi from May to December 2019. 224 participants were selected by house to house visit by simple random sampling. A pre-tested, semi-structured tool was used to collect information regarding socio-demography. Visual acuity was measured by Snellen’s chart. Vision-related quality of life was assessed using Indian Vision function questionnaire-33 (IND-VFQ-33) in all three domains. Results: About 20.1% of participants were found having VI. It was found more among those who were not working age adjusted odds ratio (AOR)=22.3, 95% confidence interval (CI)=3.2-152.2, and those who were past chewer (AOR=5.54, 95% CI=1.75-17.4). The mean total visual function score was found 108.40 (5.10) among visually impaired participants. The mean and median of these scores were found higher among participants with VI. Conclusions: One out of every 5 older adults are suffering from VI. It affects quality of life significantly. Early screening, counselling and timely referral along with accessible and affordable quality eye care service should be promoted.